Monetary Policy and Polish Labour Market in the years 1999-2008; Polityka pieniezṅa a rynek pracy w Polsce w latach 1999-2008 - Tomasz Grabia (Comparative Economic Research. Central and Eastern Europe, 2010)
This article sets out to analyse how the monetary policy pursued by the National Bank of Poland (NBP) determined the labour market situation in the country in the decade 1999-2008. The article consists of introduction as well as five sections. Section one discusses NBP's strategy of monetary policy in the defined period against monetary strategies implemented in other countries. Section two uses the growth rates of money supply and of real GDP to verify whether the primary purpose of monetary policy, i.e. the inflationary target, was achieved. Section three generally characterises the country's labour market using the levels and dynamics of employment and of unemployment. Section four discusses major instruments of NBP's monetary policy, mainly analysing changes in the central bank's interest rates and their effect on the economic situation and on the labour market. The article concludes with a summation providing synthetic conclusions. – – Celem artykułu jest analiza wpływu polityki monetarnej Narodowego Banku Polskiego (NBP) na sytuacje na rynku pracy w Polsce w ciagu dekady obejmujacej lata 1999-2008. Opracowanie składa sie z wprowadzenia oraz pieciu czesći. W pierwszej z nich omoẃiona została strategia polityki monetarnej NBP w badanym okresie wraz z poroẃnaniem ze strategia przyjmowana w innych krajach. W czesći drugiej sprawdzono, czy realizowany był podstawowy cel polityki monetarnej, czyli cel inflacyjny, w konteksćie kształtowania sie stoṕ wzrostu podazẏ pieniadza oraz realnego PKB. W punkcie kolejnym ukazana została ogoĺna charakterystyka rynku pracy na podstawie kształtowania sie poziomu i dynamiki zatrudnienia oraz bezrobocia. W czesći czwartej omoẃiono podstawowe instrumenty polityki pieniezṅej NBP. Uwaga skoncentrowana została głoẃnie na analizie zmian stoṕ procentowych banku centralnego oraz ich wpływu na sytuacje gospodarcza i rynek pracy. Całosćźamknieta została podsumowaniem, w ktoŕym zawarto syntetyczne wnioski konćowe.
Keywords: 330